Long-read sequencing unveils IGH-DUX4 translocation into the silenced IGH allele in B-cell acute lymphoblastic leukemia - Liqing Tian (Nature Portfolio, 2019)
The IGH@ proto-oncogene translocation is a known genomic driver in several blood cancers. Here, the authors show that IGH-DUX4 translocation occurs on the silenced IGH allele avoiding toxic high-level expression of DUX4 in B-ALL.